Cationic covalent organic nanosheets for rapid and effective detection of phenoxy carboxylic acid herbicides residue emitted from water and rice samples. (30th July 2022) - Liu, Lu; Wang, Xiao-Xing; Liu, Feng; Xu, Gui-Ju; Lin, Jin-Ming; Wang, Ming-Lin; Wu, Yong-Ning; Zhao, Ru-Song; Wang, Xia
Highlights: A fast and sensitive method was established for the determination of PCAs. A functional TpTGCl with abundant positive charge, N/O groups was prepared. An in-depth understanding of adsorption mechanism was elucidated by DFT study. This d-SPE technique was used to quantify PCAs in rice and water samples. Abstract: Development of efficient and sensitive adsorbent for capturing phenoxy carboxylic acids (PCAs) from environmental and food samples is necessary because PCAs could threaten human health. Designing nanoparticle with multiple functional groups is beneficial to achieve the strong adsorption interaction and the specific recognition for target compound. In this paper, TpTGCl as an ionic covalent organic framework (ICOF), that could offer plenty of positive charges and hydrogen-bonding sites, was fabricated. TpTGCl achieved quicker, more sensitive enrichment for anionic PCAs. The analysis of binding affinity by density functional theory (DFT) demonstrated that PCAs bonded to TpTGCl primarily via electrostatic attraction, N H···O and O H···O, and C H···π interaction. The quantitative approach indicated low limits of detection (0.016–0.036 ng·g −1 for rice and 0.43–0.78 ng·L -1 for water). Furthermore, successfully determining PCAs emitted from real samples indicated the applicability of TpTGCl .